How Do We Teach Planning to Pre-service Teachers – A Tentative Model. Issue 6 (18th August 2021) - Karlström, Matti; Hamza, Karim
ABSTRACT: We present an empirically based model for teaching about planning in pre-service science teacher education as part of on-campus courses. Planning is usually taught through the introduction of theoretically based planning models, but these models commonly assume a linear idea of planning that does not match how teachers go about planning. We examined how pre-service middle school science teachers planned a 20-minutes microteaching lesson on sustainable development. Six groups of pre-service teachers' conversations were video recorded, transcribed, and analyzed through practical epistemology analysis and deliberative educational questions, with the aim of extracting empirically based components of a model for teaching about planning. Our results confirm that the pre-service teachers' planning did not constitute a linear process. However, it still had certain regularities. In particular, all components of the planning model reappeared frequently, but were successively dealt with in new ways. Moreover, the pre-service teachers dealt with aspects of planning beyond those of the original model. These aspects concerned questions about (1) planning rules, (2) inauthenticity and (3) sources. We interpreted these aspects as additional components which, together with the original planning model, may constitute the beginnings of a general model for how to teach about planning in science teacher education.